(untitled) (World of finance, 2021)
Introduction. Global transformation processes, the globalization of the financial sphere in particular, which have intensified at the turn of the XX – XXI centuries, created new preconditions for the economization of international relations and the expansion of classical diplomatic tools (including economic and financial) for the foreign policy of individual actors in international relations. Orthodox approaches are being replaced by the realization that financial diplomacy is the basis for forming the economic image of the state; the institution of promoting national interests outside states and integration associations; the form of political influence and foreign economic policy; as well as a public-private partnership in international affairs. A huge variety of interests and contradictions are intertwined when talking about financial diplomacy. In this sense, the study of financial diplomacy involves going beyond the disciplinary division of social sciences and necessities of the formation of the generalization theory principles, which would be adequate to modern transformations in the system of international relations. The purpose of the article is to scientifically argue the need to apply the concept of "financial diplomacy" in scientific circulation; based on the logic of methodological monism, to reveal the interdisciplinary nature of financial diplomacy as a new independent object of economic diplomacy, which requires deepening the conceptual foundations and expanding its application in practice. Methods: scientific synthesis, interdisciplinary exchange, cross-sectional research, integrated thinking. Results. It has been found that financial diplomacy is an insufficiently discussed concept in science. It is argued that financial diplomacy, as an interdisciplinary phenomenon, should be considered in the context of interdisciplinary discourse at the conceptual and empirical levels, combining pragmatism of politics, the rationality of economics, and the art of diplomacy. At the conceptual level, it is proposed to consider financial diplomacy as an important component of economic diplomacy and as an independent area of diplomatic practice, formed under the influence of systemic determinants of global development. At the empirical level, financial diplomacy is a multidisciplinary institution of diplomacy. Within this paper models, forms, and levels of financial diplomacy are singled out; its universal methods are supplemented by specific tools; emphasis is placed on the problems of forming a modern network structure of financial diplomacy at both the formal and informal levels. Conclusions. The objective necessity of separating financial diplomacy into a separate specific branch of modern diplomatic activity is scientifically substantiated; its interdisciplinary nature is revealed and a polymodal concept of research at the conceptual and empirical levels is proposed.